Occupational Niches and the Dark Triad Traits - JONASON, Peter K. (Institutional Knowledge at Singapore Management University, 2014)
Our research focused on the vocational interests correlated with the Dark Triad traits (i.e., narcissism, psychopathy, and Machiavellianism). By understanding how these traits facilitate the structuring of one’s environment, we hypothesized that psychopaths will be more interested in realistic and practical careers, narcissists will be more interested in artistic, enterprising, and social careers, and Machiavellians will be more interested in avoiding careers that involve caring for others. In two cross-sectional studies (N = 424; N = 274), we provide general support for these hypotheses. Overall, our study showed those high on the Dark Triad traits may structure their social environment through idealized career preferences. We also show that sex differences in career preferences might be a function, in part of, individual differences in the Dark Triad traits.